Pengembangan Media Dart Board Untuk Meningkatkan Hasil Belajar Ipa Kelas Ii Di Sdit Al Akbar Karanggayam Srengat Blitar - Siti Khumairo’ Yuli Al-Manik (LPPM IAI Hasanuddin Pare-Kediri, 2021)
The aim of this study was to explore how the process of developing and testing the feasibility of the Dart Board as a learning medium to improve student learning outcomes in class II science subjects at SDIT Al Akbar Karanggayam Srengat Blitar. The research method used is research and development (R & D), which is a research method used to produce certain products and to test the effectiveness of these products. The results showed that the effect of using dart board media on student learning outcomes in class II-B showed the percentage of completeness by looking at the comparison before and after using dart board media, namely before treatment with dart board media was 8.33% so that there were 91.6% students who had not complete. However, after receiving treatment using dart board media, it increased to 87.5% and of course 12.5% of students were categorized as incomplete.